Associations of early childhood caries with salivary beta defensin-3 and childhood anemia: a case-control study - Sanam Faheem; Shahida Maqsood; Arshad Hasan; Fouzia Imtiaz; Faheem Shaikh; Waqas Ahmed Farooqui (BMC, 2021)
Abstract Background Human beta defensin-3 (HβD-3) is an antimicrobial peptide present in saliva that protects tooth surfaces from microbial attack. These peptides are part of innate immunity so levels may be affected by different systemic diseases like anemia. Therefore, anemia may predispose an affected child to an increased risk of dental caries. The objectives of this study were to determine the association of early childhood caries (ECC) with HβD-3 levels and observe the association of HβD-3 levels with childhood anemia. Methods A total of 80 children admitted in a pediatric medical ward, age 48-71 months, of either sex were included in the study. The included children were categorized as cases (children with ECC n = 40) and controls (children without ECC n = 40). Children were further segregated into the anemic and non-anemic sub-groups based on the hospital record of hemoglobin level. The salivary concentration of HβD-3 was measured by Enzyme-Linked Immuno-sorbent assay (ELISA). IBM SPSS version 20 software was used for statistical analysis. Two sample t-test and one-way ANOVA were used to compare mean values while spearman was used for correlations at p < 0.05. Results The mean Salivary HβD-3 level in cases (8.87 ± 4.30) was significantly higher (p = 0.042) as compared to controls (7.23 ± 2.57). Salivary HβD-3 level in patients with caries and without anemia was highest (10.80 ± 4.50) whereas salivary HβD-3 level in the presence of caries and anemia was lowest (6.94 ± 3.13) amongst all groups. This difference was statistically significant (p = 0.001). Salivary HβD-3 level was found to be moderately correlated with cases (p = 0.002). An inverse correlation was found between salivary HβD-3 level and anemia (r = -0.479, p = 0.002). Conclusion Anemia may affect the innate immunity of children, and may result in a decreased level of salivary HβD3, thus increasing vulnerability to decay.